2021
DOI: 10.3892/etm.2021.9772
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid B protects against acute and chronic liver injury by inhibiting Smad2C/L phosphorylation

Abstract: Salvianolic acid B (Sal B) has strong antioxidant and anti-fibrosis effects, which are related to the transforming growth factor β/Smad signaling pathway. However, how Sal B affects this antioxidant pathway and the phosphorylation (p-) of Smad2 at both the COOH-terminal (pSmad2C) and linker region (pSmad2L) are unknown. The aims of the present study were to investigate the underlying mechanisms of Sal B on acute and chronic liver injury induced by CCl 4 and H 2 O 2 , and its effects on p-Smad2C/L. In in vivo e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…roots and rhizomes in both the Chinese Pharmacopoeia and United States Pharmacopoeia. This phytochemical has revealed multiple bioactivities including (1) a protective effect on the brain from ischemia/reperfusion-induced injury by inhibiting reactive oxygen species (ROS)-mediated inflammation [ 205 ]; (2) a protective effect on the liver from acute and chronic injury by the inhibition of Smad2C/L phosphorylation [ 206 ]; (3) an anti-inflammatory effect on atherosclerosis through the mitogen-activated protein kinase/nuclear factor-κB (MAPKs/NF-κB) signaling pathways in vivo and in vitro [ 207 ]; (4) an anti-tumor effect against human breast cancer adenocarcinoma cells [ 208 ]; and (5) anti-diabetic effects [ 209 ].…”
Section: Natural Derivatives In Plantsmentioning
confidence: 99%
“…roots and rhizomes in both the Chinese Pharmacopoeia and United States Pharmacopoeia. This phytochemical has revealed multiple bioactivities including (1) a protective effect on the brain from ischemia/reperfusion-induced injury by inhibiting reactive oxygen species (ROS)-mediated inflammation [ 205 ]; (2) a protective effect on the liver from acute and chronic injury by the inhibition of Smad2C/L phosphorylation [ 206 ]; (3) an anti-inflammatory effect on atherosclerosis through the mitogen-activated protein kinase/nuclear factor-κB (MAPKs/NF-κB) signaling pathways in vivo and in vitro [ 207 ]; (4) an anti-tumor effect against human breast cancer adenocarcinoma cells [ 208 ]; and (5) anti-diabetic effects [ 209 ].…”
Section: Natural Derivatives In Plantsmentioning
confidence: 99%
“…On the one hand, the activation of Nrf2 could effectively inhibit the occurrence of LF, but on the other hand, sustained activation of Nrf2 may promote liver injury and further induce LF and the occurrence of liver cancer. [48,49] Fauconneau et al reported that under oxidative stress conditions, HO-1, as a downstream target of Nrf2, its expression level was increased. [50] However, Tan IIA may effectively inhibit LF by reducing the expression level of HO-1, [51] which was consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with salvianolic acid B inhibits the phosphorylation of Smad2 both at the C-terminus and link region via the TGF-β/Smad signaling pathway, improves the histological characteristics of the liver, decreases the levels of aspartate aminotransaminase (AST) and alanine aminotransferase (ALT), and attenuates oxidative stress (increased SOD levels and decreased GSH levels) to protect against acute and chronic liver injury. In addition, upregulation of the Nrf2/HO-1 signaling pathway by salvianolic acid B plays a key role in suppressing CCl 4 -induced acute liver injury [ 154 , 155 ]. In mouse models of senecionine-induced acute liver injury, salvianolic acid B can regulate oxidative stress (increased SOD levels and decreased GSH levels) and inhibit liver fibrosis-related factors, including MMP-9, TGF-β1, and phosphorylated STAT3, by modulating the coagulation system (decreased expression of plasminogen activator inhibitor 1 (PAI-1)).…”
Section: Pharmacological Effectsmentioning
confidence: 99%